Enantiomeric separation of novel anticancer agent 5-hydroxy-3-(4-methoxyphenyl)-2-(3,4,5-trimethoxyphenyl)-cyclopent-2-en- 1-one - Shinde, Popat D.; Jadhav, Vinod H.; Borate, Hanumant B.; Bhide, Sunil R.; Sonawane, Kiran B.; Wakharkar, Radhika D. (Journal of Chromatography A, 2007)
The enantiomers of 5-hydroxy-3-(4-methoxyphenyl)-2-(3,4,5-trimethoxyphenyl)-cyclopent-2-en- 1-one, a novel anticancer agent, were separated by derivatisation with caronaldehyde, separation of the resulting diastereoisomers of the corresponding esters by silica gel column chromatography and regeneration of alcohols (S)-5-hydroxy-3-(4-methoxyphenyl)-2-(3,4,5-trimethoxyphenyl)-cyclopent-2 -en-1-one and (R)5-hydroxy-3-(4-methoxyphenyl)-2-(3,4,5-trimethoxyphenyl)-cyclopent-2- en- 1-one under aqueous conditions. The absolute configuration of the enantiomers was determined by H-1 NMR studies of the corresponding Mosher esters. Alternatively, the enantiomers were separated by preparative HPLC to collect the (S)- and (R)-5-hydroxy-3-(4-methoxyphenyl)-2-(3,4,5-trimethoxyphenyl)-cyclopent-2 -en-1-ones with high purity which was comparable with that obtained by the chemical method. The details of these methods have been presented herein. (c) 2006 Elsevier B.V. All rights reserved.
Keywords: Anticancer; column chromatography; diaryl cyclopentenone; diastereoisomers; enantioseparation; HPLC; Resolution

Two new eudesmanolides from sphaeranthus indicus (Linn) - Jadhav, Ravindra B.; Sonawane, Kiran B.; Deshpande, Nirmala R.; Rojatkar, Supada R. (Indian Journal of Chemistry Section B-Organic Chemistry Including Medicinal Chemistry, 2007)
Two new eudesmanolides have been isolated from the aerial part of Sphaeranthus indicus and their structures have been established as 11 alpha,13-dihydro-3 alpha,7 alpha-dihydroxyeudesm-4-en 6 alpha, 12-olide 1, 4-en-6 beta,7 alpha-eudesmanolide 3, on the basis of spectral data and comparison of spectral data with those of reported data of compounds 2, 4 and 5.
Keywords: eudesmanolides; olide; Sphaeranthus indicus

Isolation, characterization and antihyperlipidemic activity of secoisolariciresinol diglucoside in poloxamer-407-induced experimental hyperlipidemia - Zanwar, Anand A.; Hegde, Mahabaleshwar V.; Rojatkar, Supada R.; Sonawane, Kiran B.; Rajamohanan, P. R.; Bodhankar, Subhash L. (Pharmaceutical Biology, 2014)
Context: Linum usitatissimum L. (Linaceae), commonly known as flaxseed, is a good source of dietary fiber and lignans. Earlier we reported cardioprotective, antihyperlipidemic, and in vitro antioxidant activity of flax lignan concentrate (FLC) obtained from flaxseed. Objectives: To isolate secoisolariciresinol diglucoside (SDG) from FLC and to evaluate the antihyperlipidemic activity of SDG in poloxamer-407 (P-407)-induced hyperlipidaemic mice. Material and methods: FLC was subjected to column chromatography and further subjected to preparative HPTLC to isolate SDG. The chemical structure of the isolated compound was elucidated by UV, IR, H-1 NMR, C-13 NMR, DEPT, COSY, HSQC, HMBC, ROESY, MS, and specific optical rotation was recorded. Further, we have investigated the antihyperlipidaemic effect of SDG (20 mg/kg) in P-407-induced hyperlipidaemic rats. Hyperlipidaemia was induced by intraperitoneal administration of P-407 (30% w/v). Serum lipid parameters such as total cholesterol (TC), triglycerides (TG), and high-density lipoprotein cholesterol (HDL-C) levels were measured. Results and discussion: The structure and stereochemistry of the isolated compound were confirmed on the basis of 1D and 2D spectral data and characterized as SDG. Finally, isolated pure SDG was screened using a P-407-induced mice model for its antihyperlipidemic action using serum lipid parameters. The isolated SDG (20 mg/kg) significantly reduced serum cholesterol, triglyceride (p<0.001), very low-density lipoprotein (p<0.05), and non-significantly increased HDL-C. Conclusion: Finally, it was concluded unequivocally that SDG showed antihyperlipidaemic effects in P-407-induced hyperlipidaemic mice. Isolated pure SDG confirms that SDG is beneficial in the prevention of experimental hyperlipidemia in laboratory animals.
Keywords: column chromatography; flaxseed; Linum usitatissimum

Synthesis of (+/-)-thia-calanolide A, its resolution and in vitro biological evaluation - Chopade, Anil U.; Chopade, Manojkumar U.; Chanda, Bhanu M.; Sawaikar, Dilip D.; Sonawane, Kiran B.; Gurjar, Mukund K. (Arabian Journal of Chemistry, 2016)
A synthesis of (+/-)-thia-calanolide A 3 has been successfully accomplished starting from 3,5-dimethoxythiophenol 4, in six steps in an overall yield of 4.5%. The key reaction involved Friedel-Crafts tigloylation of 5,7-dihydroxy-4-n-propyl thiocoumarin 6 employing an appropriate solvent of CS2-PhNO2 in a ratio of 7:3. In its biological evaluation for anti-HIV activity, (+/-)-thia-calanolide A 3 demonstrated comparatively less activity with calanolide A and its synthetic analogue aza-calanolide. Further, (+/-)-3 has been resolved by chiral HPLC to (+) and (-)-3. (C) 2012 Production and hosting by Elsevier B.V. on behalf of King Saud University.

Exploring the potential of Desmodium gangeticum (L.) DC. extract against spatial memory deficit in rats - Changdar, Nilanjan; Ganjhu, Rajesh Kumar; Rijal, Samita; Kumar, Ayush; Mallik, Shanchari Basu; Nampoothiri, Madhavan; Shenoy, Rekha R.; Sonawane, Kiran B.; Rao, Mallikarjuna C.; Mudgal, Jayesh (Pharmacognosy Magazine, 2019)
Background: A few published reports demonstrated the neuroprotective effect of Desmodium gangeticum (L.) DC. in an acute model of dementia. Objective: The purpose of the present study was to evaluate the preclinical efficacy of D. gangeticum against chronic dementia when administered prophylactically. Materials and Methods: Chronic spatial memory deficit was induced in rats by aluminum chloride (AlCl3, 10 mg/kg, i.p.). Treatment with hydroalcoholic whole plant extract of D. gangeticum (DG extract) was initiated 2 week before AlCl3 challenge and continued till the 51(st) day after the challenge, orally at the dose of 400 mg/kg/day. The spatial memory was assessed by Morris water maze test. Hippocampal and frontal cortex acetyl cholinesterase (AChE) and oxidative stress were assessed in diseased rat brains. Results: Chronic administration of AlCl3 produced spatial memory deficit in rats. Memory impairment was manifested in rats as an increase in escape latency and D-quadrant latency whereas a decrease in total time spent in D-quadrant. These behavioral alterations were reversed significantly by the treatment with DG extract. In addition, DG extract significantly increased the island time, indicating memory improvement. DG extract corrected the declined AChE in frontal cortex and altered frontal cortex/hippocampus catalase activity. Phytochemical investigation of the DG extract revealed large content of saponins among the other phytochemicals such as tannins, alkaloids, and flavonoids. Conclusion: These results indicate the possible prophylactic potential of saponin-rich DG extract against chronic memory deficit in rats.
Keywords: Acetyl cholinesterase; Aluminum chloride; dementia; Desmodium gangeticum (L) DC; Oxidative stress